Slurry for additive manufacturing and method for manufacturing three-dimensional additively manufactured object
The slurry formulation with specific inorganic particle sizes and dispersant ratios addresses thixotropy issues, enabling high-precision and stable production of three-dimensional layered products by ensuring uniform film thickness and shape maintenance.
Patent Information
- Application Number
- JP2021150135
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-15
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-09-15
AI Technical Summary
Existing slurries for additive manufacturing face challenges in achieving uniform film thickness and maintaining shape stability due to insufficient thixotropy, particularly when using inorganic particles with small diameters, leading to agglomeration and difficulty in producing high-definition, precise three-dimensional layered products.
A slurry formulation comprising inorganic particles with an average diameter of 0.1 μm to 5.0 μm, a dispersant ratio of 95% nonionic to 5% ionic dispersant, and viscosity ratios that ensure thixotropy, allowing for high precision and stability in layer formation.
The solution enables the production of three-dimensional layered products with uniform coating films and maintained shape, achieving high precision and stability by optimizing dispersant ratios and viscosity characteristics.
Smart Images

Figure 0007608303000003 
Figure 0007608303000004 
Figure 0007608303000005
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a slurry for additive manufacturing and a method for manufacturing a three-dimensional additive manufactured object. [Background technology]
[0002] When producing a three-dimensional additive manufacturing object, for example, a slurry for additive manufacturing containing inorganic particles (such as ceramic particles) and a liquid photocurable resin is discharged from a syringe and deposited, and then the deposited slurry for additive manufacturing is smoothed with a squeegee to form a slurry film, which is irradiated with light to cure the photocurable resin, thereby forming a hardened layer. The formation of the hardened layer is repeatedly performed based on the three-dimensional design data of the three-dimensional additive manufacturing object, and a stack of hardened layers is produced. Then, for example, a degreasing process is performed on the stack of hardened layers to remove the hardened photocurable resin, and a sintering process is performed to sinter the inorganic particles, thereby producing a three-dimensional additive manufacturing object. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-132092 A [Patent Document 2] JP 2019-1686 A [Patent Document 3] JP 2017-31490 A [Patent Document 4] JP 2014-83744 A [Patent Document 5] WO2018 / 043413 Summary of the Invention [Problem to be solved by the invention]
[0004] When producing a three-dimensional additive manufacturing object as described above, it is necessary that the thickness of the slurry film after the deposit of the additive manufacturing slurry is smoothed with a squeegee is uniform. At the same time, it is necessary that the shape of the slurry film is maintained before curing by irradiation with light. For this reason, the additive manufacturing slurry is required to have thixotropy, that is, high viscosity at low shear rates and low viscosity at high shear rates.
[0005] However, in the past, it was sometimes difficult to achieve sufficient thixotropy in the slurry for additive manufacturing. In particular, when inorganic particles with a small particle size are used to achieve high-definition modeling, the inorganic particles are likely to aggregate in the slurry for additive manufacturing, and the thixotropy of the slurry for additive manufacturing may become insufficient. As a result, it may be difficult to stably produce a three-dimensional additive manufacturing object with high precision.
[0006] Therefore, the problem that the present invention aims to solve is to provide a slurry for additive manufacturing, which makes it possible to easily produce three-dimensional additive objects with high precision and stability, and a method for manufacturing three-dimensional additive objects. [Means for solving the problem]
[0007] The additive manufacturing slurry of the embodiment is used when producing a three-dimensional additive manufacturing object, and contains inorganic particles, a liquid photocurable resin, and a dispersant. The inorganic particles have an average particle size R that satisfies the relationship of 0.1 μm≦R≦5.0 μm. The dispersant contains a nonionic dispersant and an ionic dispersant, and the ratio W1:W2 of the weight W1 of the nonionic dispersant to the weight W2 of the ionic dispersant satisfies the relationship of 95 wt%:5 wt%≦W1:W2≦10 wt%:90 wt%. The additive manufacturing slurry of the embodiment is used when a shear rate is 0.5 s -1 Viscosity η when 0.5 and the shear rate is 10 s -1 Viscosity η when 10 And, η 0.5 ≧40 [Pa s], η 10 ≦340[Pa·s], and η0.5 / η 10 ≧2. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a flow diagram showing an overview of a method for producing a three-dimensional layered object according to an embodiment. [Figure 2A] FIG. 2A is a diagram that illustrates an overview of the hardened layer forming step (ST20) in the method for producing a three-dimensional additive manufacturing object according to the embodiment. [Figure 2B] FIG. 2B is a diagram that illustrates an overview of the hardened layer forming step (ST20) in the method for producing a three-dimensional additive manufacturing object according to the embodiment. [Figure 2C] FIG. 2C is a diagram that illustrates an overview of the hardened layer forming step (ST20) in the method for producing a three-dimensional additive manufacturing object according to the embodiment. [Figure 2D] FIG. 2D is a diagram that illustrates an overview of the hardened layer forming step (ST20) in the method for producing a three-dimensional additive manufacturing object according to the embodiment. [Figure 3A] FIG. 3A is a diagram showing a state before a degreasing step (ST30) is performed in the method for manufacturing a three-dimensional laminated object according to the embodiment. [Figure 3B] FIG. 3B is a diagram showing a state after a degreasing step (ST30) has been performed in the method for manufacturing a three-dimensional laminated object according to the embodiment. [Figure 3C] FIG. 3C is a diagram showing a state after the sintering step (ST40) has been performed in the method for manufacturing a three-dimensional laminated object according to the embodiment. [Figure 4] FIG. 4 shows the results of viscosity measurement of each example of slurry for additive manufacturing under multiple conditions with different shear rates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [A] Manufacturing method A method for manufacturing a three-dimensional layered object according to an embodiment will be described.
[0010] FIG. 1 is a flow diagram showing an overview of a method for producing a three-dimensional layered object according to an embodiment.
[0011] As shown in Fig. 1, the three-dimensional additive manufacturing process is carried out by sequentially carrying out a preparation process (ST10), a hardened layer forming process (ST20), a degreasing process (ST30), and a sintering process (ST40). The three-dimensional additive manufacturing process is carried out using a modeling device (e.g., model SZ-1100 manufactured by Shashin Kagaku Co., Ltd.). Each process will be described in turn.
[0012] [A-1] Preparation process (ST10) First, in the preparation step (ST10), a slurry for additive manufacturing to be used when manufacturing a three-dimensional additive manufacturing object is prepared.
[0013] The slurry for additive manufacturing is prepared by mixing inorganic particles, a liquid photocurable resin, and a dispersant.
[0014] [A-1-1] Inorganic particles The inorganic particles are, for example, ceramic particles made of alumina, zirconia (including yttria-stabilized zirconia), etc. The inorganic particles may be metal particles made of a metal material.
[0015] Here, inorganic particles are used whose average particle diameter R satisfies the relationship shown in the following formula A. The average particle diameter R is the 50% volume average particle diameter (D50 diameter), which corresponds to the particle diameter at which the integrated value is 50% in the particle size distribution measured based on the laser scattering diffraction method (JIS Z 8825:2013).
[0016] 0.1μm≦R≦5.0μm (Formula A)
[0017] When the average particle size R of the inorganic particles is smaller than the lower limit of the range shown in (Formula A), the inorganic particles are likely to aggregate in the slurry for additive manufacturing, which may reduce the applicability of the slurry for additive manufacturing. On the other hand, when the average particle size R of the inorganic particles is larger than the upper limit of the range shown in (Formula A), the density of the three-dimensional additive manufacturing object produced after the sintering step (ST40) may decrease.
[0018] In the slurry for additive manufacturing, the inorganic particles are preferably in the range of 25% by volume or more and 70% by volume or less. If the content of the inorganic particles is less than the above range, the thixotropy of the slurry for additive manufacturing may be insufficient, and the density of the three-dimensional additive manufacturing object produced after the sintering step (ST40) may decrease. On the other hand, if the content of the inorganic particles is greater than the above range, there may be many inorganic particles that are not dispersed in the slurry for additive manufacturing.
[0019] [A-1-2] Photocurable resin The liquid photocurable resin contains a polymerizable component, such as a monomer or an oligomer, and a photopolymerization initiator for initiating polymerization of the polymerizable component when irradiated with light. The polymerizable component is, for example, an acrylic monomer.
[0020] [A-1-3] Dispersant The dispersant is added to disperse inorganic particles in the liquid photocurable resin. The content of the dispersant is preferably 0.3% by weight or more and 20% by weight or less with respect to 100% by weight of inorganic particles. If the content of the dispersant is less than the above range, the dispersibility decreases due to insufficient adhesion amount of dispersant required for inorganic particle components, and if it is more than the above range, the viscosity of the liquid components other than inorganic particles (photocurable resin, dispersant) increases, and the viscosity of the slurry increases due to depletion and aggregation.
[0021] In this embodiment, both nonionic dispersants and ionic dispersants are used as dispersants. As nonionic dispersants, for example, polyoxyethylenes, polypropylene glycols, glycerins, sorbitans, propylene glycols, polyoxyethylene sorbitans, ester ethers, diethanolamines, and the like, which are ether-type polyhydric alcohols, can be used. Among them, ester-type polyhydric alcohols are more preferable. As ionic dispersants, for example, anionic carboxylates, sulfonates, sulfates, phosphates, cationic amine salts, ammonium salts, and amphoteric dispersants having anionic and cationic types in the same molecule can be used. Among them, polycarboxylic acid copolymers, which are anionic carboxylates, are more preferable.
[0022] In the slurry for additive manufacturing of this embodiment, the ratio W1:W2 of the weight W1 of the nonionic dispersant to the weight W2 of the ionic dispersant satisfies the relationship shown in the following (Formula B).
[0023] 95% by weight: 5% by weight≦W1:W2≦10% by weight: 90% by weight...(Formula B)
[0024] In the total amount (100% by weight) of the weight W1 of the nonionic dispersant and the weight W2 of the ionic dispersant, if the weight W2 of the ionic dispersant is greater than the upper limit (W2=90% by weight) shown in the above (Formula B), the shape of the slurry layer formed with the slurry for additive manufacturing in the hardened layer forming step (ST20) is difficult to maintain. In the total amount (100% by weight) of the weight W1 of the nonionic dispersant and the weight W2 of the ionic dispersant, if the weight W2 of the ionic dispersant is less than the lower limit (W2=5% by weight) shown in the above (Formula B), a uniform coating film may not be formed when the slurry for additive manufacturing is applied to form the slurry layer in the hardened layer forming step (ST20).
[0025] The additive manufacturing slurry of this embodiment contains both a nonionic dispersant and an ionic dispersant as dispersants. The nonionic dispersant adheres the dispersed components of the polymer to the surface of the inorganic particles, making them less likely to come into contact at a certain distance or less due to repulsion from steric hindrance. As a result, in the additive manufacturing slurry, the contact resistance between the inorganic particles is suppressed, improving fluidity and reducing viscosity. On the other hand, since the nonionic dispersant also has the effect of tightly entangling the polymers with each other, when added alone or in large amounts, aggregation occurs in the additive manufacturing slurry and the viscosity increases. The ionic dispersant has a high repulsive force due to steric hindrance, and when added alone or in large amounts, the additive manufacturing slurry loses its thixotropy and becomes a Newtonian fluid. As a result, by adjusting the blending of the two dispersants, it is possible to achieve the effect of achieving both thixotropy and low viscosity in the additive manufacturing slurry.
[0026] [A-1-4] Viscosity In the slurry for additive manufacturing of this embodiment, the shear rate is 0.5 s -1 Viscosity η when 0.5 , and the shear rate is 10 s -1 Viscosity η when 10 satisfies the relationships shown in the following (Equation C1), (Equation C2), and (Equation C3). Viscosity η 0.5 and viscosity η 10 is a value measured using a Brookfield viscometer at a temperature of 23°C (JIS Z 8803).
[0027] η 0.5 ≧40[Pa·s] (Formula C1)
[0028] η 10 ≦340[Pa s] (Formula C2)
[0029] η 0.5 / η 10 ≧2 (Formula C3)
[0030] Viscosity η of slurry for additive manufacturing 0.5If the above (Formula C1) is not satisfied, the shape of the slurry layer formed from the slurry for additive manufacturing in the hardened layer formation step (ST20) is difficult to maintain. 10 If the above (Formula C2) is not satisfied, when the slurry for additive manufacturing is applied to form the slurry layer in the hardened layer forming step (ST20), a uniform coating film may not be formed. 0.5 and viscosity η 10 If the above (Formula C3) is not satisfied, the thixotropy of the slurry for additive manufacturing may be insufficient.
[0031] [A-2] Hardened layer formation process (ST20) As shown in FIG. 1, after the preparation step (ST10), a hardened layer forming step (ST20) is performed.
[0032] 2A to 2D are diagrams that diagrammatically show an overview of the hardened layer forming step (ST20) in the method for producing a three-dimensional additive manufacturing object according to the embodiment.
[0033] In the hardened layer forming step (ST20), as shown in FIG. 2A, the deposit 10 deposited by discharging the additive manufacturing slurry from a syringe (not shown) is smoothed using a squeegee 100. As a result, as shown in FIG. 2B, a slurry film 20 having a uniform thickness is formed. Thereafter, as shown in FIG. 2C, the slurry film 20 is irradiated with light 200 to harden the photocurable resin constituting the slurry film 20, thereby forming a hardened layer 30. As shown in FIG. 2D, the steps shown in FIG. 2A to FIG. 2C are repeatedly performed based on the three-dimensional design data of the three-dimensional additive manufacturing object, thereby forming a laminate of the hardened layer 30 as a precursor of the three-dimensional additive manufacturing object. The unhardened portion of the slurry film 20 is removed by a cleaning process.
[0034] [A-3] Degreasing process (ST30), sintering process (ST40) As shown in FIG. 1, after the hardened layer forming step (ST20), a degreasing step (ST30) and a sintering step (ST40) are performed.
[0035] Fig. 3A is a diagram showing a state before a degreasing step (ST30) is performed in the manufacturing method of a three-dimensional additive manufacturing object according to the embodiment. Fig. 3B is a diagram showing a state after a degreasing step (ST30) is performed in the manufacturing method of a three-dimensional additive manufacturing object according to the embodiment. Fig. 3C is a diagram showing a state after a sintering step (ST40) is performed in the manufacturing method of a three-dimensional additive manufacturing object according to the embodiment. Figs. 3A to 3C are schematic diagrams showing cross sections of some of the hardened layers constituting the laminate.
[0036] 3A, the hardened layer 30 formed in the hardened layer formation step (ST20) includes inorganic particles 31 and a matrix 32. The matrix 32 is a base material, and includes a dispersant for the slurry for additive manufacturing together with a hardened component formed by hardening the photocurable resin in the slurry for additive manufacturing.
[0037] As shown in FIG. 3B, when the degreasing treatment is performed in the degreasing step (ST30), the matrix 32 is thermally decomposed and removed in the hardened layer 30 (see FIG. 3A).
[0038] 3C, in a sintering step (ST40), a sintering process is performed on the inorganic particles 31 of the laminate that has been subjected to the degreasing step (ST30), thereby sintering the inorganic particles 31. In this manner, a sintered body of the inorganic particles 31 is formed as a three-dimensional additive manufacturing object.
[0039] [B] Summary The slurry for additive manufacturing of this embodiment contains inorganic particles, a liquid photocurable resin, and a dispersant. The inorganic particles satisfy the relationship shown in (Formula A) as described above. The dispersant contains a nonionic dispersant and an ionic dispersant, and the ratio W1:W2 of the weight W1 of the nonionic dispersant to the weight W2 of the ionic dispersant satisfies the relationship shown in (Formula B) as described above. Furthermore, in the slurry for additive manufacturing of this embodiment, when the shear rate is 0.5 s -1 Viscosity η when 0.5 , and the shear rate is 10 s -1 Viscosity η when10 As described above, satisfies the relationships shown in (Formula C1), (Formula C2), and (Formula C3). Therefore, as shown in the example described later, when the slurry for additive manufacturing is applied to form the slurry layer in the hardened layer forming step (ST20), a uniform coating film can be formed, and the shape of the slurry layer formed with the slurry for additive manufacturing in the hardened layer forming step (ST20) is maintained. As a result, in this embodiment, a three-dimensional additive manufacturing object can be produced with high precision and stability. EXAMPLES
[0040] Examples of the above-mentioned embodiment will be described with reference to Fig. 4, Tables 1 and 2. In Fig. 4, Tables 1 and 2, Examples 1 to 15 are examples, and Examples C1 to C5 are comparative examples.
[0041] FIG. 4 shows the results of viscosity measurement of each example of slurry for additive manufacturing under multiple conditions with different shear rates.
[0042] In Table 1, X1 is the inorganic particle content (wt%) in the additive manufacturing slurry, X2 is the liquid photocurable resin content (wt%) in the additive manufacturing slurry, X31 is the non-ionic dispersant content (wt%) in the additive manufacturing slurry, and X32 is the ionic dispersant content (wt%) in the additive manufacturing slurry. In Table 2, W1 is the non-ionic dispersant content (wt%) relative to the inorganic particles (i.e., W1=100·X31 / X1), and W2 is the ionic dispersant content (wt%) relative to the inorganic particles (i.e., W2=100·X32 / X1).
[0043] [Table 1]
[0044] [Table 2]
[0045] [1] Preparation of slurry samples for additive manufacturing [1-1] Example 1 In Example 1, the following materials were prepared as inorganic particles, a photocurable resin, a nonionic dispersant, and an ionic dispersant.
[0046] (material) Inorganic particles: Alumina particles (average particle size 2.3 μm, made by Nippon Light Metal Co., Ltd., product number: LS-242C) Photocurable resin: Acrylic (made by Safran, product number: SPR-2120) Non-ionic dispersant: Polyhydric alcohol type non-ionic surfactant (manufactured by Sannobuco, product number: SN Dispersant 9228) Ionic dispersant: Polycarboxylic acid copolymer (anionic surfactant, NOF Corp., product number: Marialim SC-0505K)
[0047] Then, each material was mixed at the content ratios X1, X2, X31, and X32 (wt%) shown in Table 1, and the mixture was stirred under the stirring conditions described below to prepare a sample of slurry for additive manufacturing.
[0048] (Mixing conditions) Mixer: ARE-250 (Thinky) Rotation speed: 800 rpm Revolution speed: 2000 rpm Mixing time: 5 minutes
[0049] [1-2] Example 2 to Example 6, Example C3, Example C5 In Examples 2 to 6, C3, and C5, as shown in Table 1, samples of slurry for additive manufacturing were prepared in the same manner as in Example 1, except that the material content ratios X1, X2, X31, and X32 (wt%) were different from those in Example 1.
[0050] [1-3] Example 7 to Example 10, Example C1, Example C4 As shown in Table 1, in Examples 7 to 10, C1, and C4, unlike Example 1, the following materials were used as inorganic particles.
[0051] (material) Inorganic particles: Alumina particles (average particle size 1.1 μm, manufactured by Sumitomo Chemical, product number: AES-22s)
[0052] Then, each material was mixed at the content ratios X1, X2, X31, and X32 (wt%) shown in Table 1, and the mixture was stirred to prepare a sample of slurry for additive manufacturing.
[0053] [1-4] Example 11 to Example 13, Example C2 As shown in Table 1, in Examples 11 to 13, unlike Example 1, the following materials were used as inorganic particles.
[0054] (material) Inorganic particles: Alumina particles (average particle size 0.1 μm, manufactured by Taimei Chemicals, product number: TM-DAR)
[0055] Then, each material was mixed at the content ratios X1, X2, X31, and X32 (wt%) shown in Table 1, and the mixture was stirred to prepare a sample of slurry for additive manufacturing.
[0056] [1-5] Example 14 In Example 14, as shown in Table 1, unlike Example 1, the following materials were used as inorganic particles.
[0057] (material) Inorganic particles: Zirconia particles (average particle size 1.6 μm, manufactured by Daiichi Kigenso Kagaku, product number: KYZ-8)
[0058] Then, each material was mixed at the content ratios X1, X2, X31, and X32 (wt%) shown in Table 1, and the mixture was stirred to prepare a sample of slurry for additive manufacturing.
[0059] [1-6] Example 15 In Example 15, as shown in Table 1, unlike Example 1, the following materials were used as inorganic particles.
[0060] (material) Inorganic particles: Zirconia particles (average particle size 4.6 μm, Daiichi Kigenso Kagaku, product number: UZY-8)
[0061] Then, each material was mixed at the content ratios X1, X2, X31, and X32 (wt%) shown in Table 1, and the mixture was stirred to prepare a sample of slurry for additive manufacturing.
[0062] [2] Measurement of slurry viscosity As shown in FIG. 4 and Table 2, the viscosity of each sample of the slurry for additive manufacturing prepared as described above was measured.
[0063] The viscosity was measured using the following viscometer under the following temperature conditions.
[0064] Viscometer: B-type viscometer HBDV2T (manufactured by Eiko Seiki Co., Ltd.) ·Measurement temperature: 23℃
[0065] Here, viscosity measurements were performed under multiple conditions with different shear rates. Figure 4 shows the results of viscosity measurements under multiple conditions with different shear rates. In addition, Table 2 shows the results for the shear rate of 0.5 s -1 Viscosity η when 0.5 The results are shown in Table 1. -1 Viscosity η when 10 In addition, in Table 2, the results are shown for the shear rate of 0.5 s -1 Viscosity η when 0.5 When the shear rate is 10 s -1 Viscosity η when 10 Divided by (η 0.5 / η 10 ) is shown.
[0066] [3] Test Contents As shown in Table 2, a test for shape retention and a test for coatability were carried out for each example of the slurry for additive manufacturing prepared as described above.
[0067] [3-1] Shape retention test In the shape retention test, a groove was formed in the slurry for additive manufacturing contained inside the container by sliding a spatula horizontally inside the container, which contained the slurry for additive manufacturing with a uniform thickness (5 mm), so that the bottom of the container was visible. Then, 60 seconds after the spatula was slid, the state of the groove was visually observed. The proportion of the width of the groove that was maintained was then determined according to the following ranking criteria to determine the shape retention proportion of the slurry.
[0068] Rank 5: 0% width loss (100% shape retention) Rank 4: Width reduction is greater than 0% and less than 25% Rank 3: Width reduction is between 25% and 60% Rank 2: Reduction in width is between 60% and 95% (within practical level) Rank 1: Width reduction exceeds 95% (not practical level)
[0069] [3-2] Coating property test In the test for coatability, a slurry film was formed on the coating surface using each example of the additive manufacturing slurry, and then the slurry film was smoothed to a thickness of 30 μm by moving a squeegee on the coating surface. Here, the smoothing of the slurry film was performed under conditions of squeegee movement speeds of 1 mm / s, 5 mm / s, 10 mm / s, and 25 mm / s. The state of the slurry film after smoothing was then visually observed, and the observation results were judged as coatability according to the following ranking criteria.
[0070] Rank 5: Squeegee speed is 25mm / s or less and the slurry film is uniform Rank 4: Squeegee movement speed is 10mm / s or less and the slurry film is uniform Rank 3: Squeegee speed is 5mm / s or less and the slurry film is uniform Rank 2: Squeegee movement speed is 1mm / s or less and the slurry film is uniform (within practical level) Rank 1: Even when the squeegee moving speed is 1mm / s or less, the slurry film is not uniform (not practical).
[0071] [4] Test results As can be seen from Table 1, Examples 1 to 15 satisfy the relationships (see below) shown in (Formula A), (Formula B), (Formula C1), (Formula C2), and (Formula C3) described above.
[0072] 0.1μm≦R≦5.0μm (Formula A) 95% by weight: 5% by weight≦W1:W2≦10% by weight: 90% by weight...(Formula B) η 0.5 ≧40[Pa·s] (Formula C1) η 10 ≦340[Pa s] (Formula C2) η 0.5 / η 10 ≧2 (Formula C3)
[0073] For this reason, sufficient thixotropy was obtained in Examples 1 to 15, as shown in Figure 4. As a result, as shown in Table 2, shape retention properties and coatability at or above the practical level (rank 2 or higher) were obtained in Examples 1 to 15.
[0074] In contrast, Example C1 does not satisfy the relationships shown in (Formula B) and (Formula C2) as can be seen from Table 1. Therefore, in Example C1, the thixotropy is insufficient as shown in FIG. 4, and the coatability is lower than the practical level (rank 2 or higher) as shown in Table 2.
[0075] As can be seen from Table 1, Example C2 does not satisfy the relationship shown in (Equation B). Therefore, in Example C2, as shown in FIG. 4, -1 As a result, in Example C2, as shown in Table 2, the shape retention property could not be determined, and the coatability was lower than the practical level (rank 2 or higher).
[0076] As can be seen from Table 1, Examples C3 and C4 do not satisfy the relationship shown in (Formula B) and (Formula C1). Therefore, in Examples C3 and C4, the thixotropy was insufficient (liquefaction) as shown in Figure 4. As a result, in Examples C3 and C4, the shape retention property was lower than the practical level (rank 2 or higher) as shown in Table 2, and the coatability could not be judged.
[0077] As can be seen from Table 1, Example C5 does not contain a dispersant and does not satisfy the relationship shown in (Formula B). Therefore, in Example C5, the sample was in a solidified state and the viscosity could not be measured. As a result, in Example C5, as shown in Table 2, the shape retention property could not be determined, and the applicability was lower than the practical level (rank 2 or higher).
[0078] <Other> Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0079] 10: deposit, 20: slurry film, 30: hardened layer, 31: inorganic particles, 32: matrix, 100: squeegee, 200: light
Claims
1. A slurry for additive manufacturing used in producing a three-dimensional additive manufacturing object, Inorganic particles; A liquid photocurable resin; Dispersant and having The inorganic particles have an average particle size R that satisfies the relationship 0.1 μm≦R≦5.0 μm, The dispersant is A non-ionic dispersant; Ionic dispersants and The ratio W1:W2 of the weight W1 of the nonionic dispersant to the weight W2 of the ionic dispersant satisfies the relationship of 95% by weight:5% by weight≦W1:W2≦10% by weight:90% by weight, Shear rate is 0.5 s -1 Viscosity η when 0.5 and the shear rate is 10 s -1 Viscosity η when 10 And, η 0.5 ≧40 [Pa・s], η 10 ≦340 [Pa s], and η 0.5 / 10 ≧2. Slurry for additive manufacturing.
2. The inorganic particles are present in an amount of 25% by volume or more and 70% by volume or less. The additive manufacturing slurry according to claim 1 .
3. A method for producing a three-dimensional laminated object, comprising the steps of: producing a three-dimensional laminated object using the slurry for laminated object production according to claim 1 or 2; A preparation step of preparing the slurry for additive manufacturing; a hardened layer forming step of forming a hardened layer by irradiating light onto the slurry film obtained by smoothing the deposit of the slurry for additive manufacturing to harden the photocurable resin; having The hardened layer forming step is repeatedly performed based on three-dimensional design data of the three-dimensional additive manufacturing object to form a stack of the hardened layers. A method for manufacturing three-dimensional additively manufactured objects.
4. a degreasing process for removing the cured photocurable resin by performing a degreasing process on the laminate including the cured layer; a sintering step of sintering the inorganic particles by performing a sintering process on the laminate that has been subjected to the degreasing step; having The method for producing a three-dimensional layered object according to claim 3 .
Citation Information
Patent Citations
Developing liquid composition for 3D printing molded object
JP2014083744A
Method for manufacturing three-dimensional molded object, apparatus for manufacturing three-dimensional molded object, three-dimensional molded object, and composition for manufacturing three-dimensional molded object
JP2017031490A
Slurry for lamination molding and method for manufacturing three-dimensional laminated molding
JP2017132092A
Method for manufacturing three-dimensional object, and apparatus for manufacturing three-dimensional object
JP2018187893A
Coating slurry for lamination molding and three-dimensional shaped article
JP2019001686A
